Predictors of Internet Use among Older Adults in Lithuania - Sadauskaitė, Raimonda; Kairys, Antanas; Jurevičiūtė, Ieva; Zamalijeva, Olga; Kalnina, Diana; Rajevska, Olga; Reine, Ieva (Information & Media, 2025)
Introduction. The internet is essential to daily life by virtue of bridging age gaps and enhancing communication, information access, and social participation. Research has linked it to various positive outcomes, such as better psychological well-being. However, internet use among older adults in Lithuania is still below the European average. Therefore, this research examined various predictors of internet use among older Lithuanian adults. Methods. Data from Wave 8 and Wave 9 COVID-19 Survey 2 of the Survey of Health, Ageing and Retirement in Europe (SHARE) were analyzed. By using probability sampling, the study ensured a representative sample of 626 Lithuanian respondents aged 65 and older. Self-reported internet use for any reason was used in the analysis as the outcome variable. Personality traits were measured using the 10-item Big Five Inventory. Several health indicators, chronological and subjective age discrepancy, and sociodemographic characteristics were also assessed. Results. Logistic regression analysis revealed that age, place of residence, feeling younger than one’s actual age, and agreeableness as a personality trait predicted the likelihood of internet use. The study offers valuable insights into the predictors of internet use among older Lithuanian adults, while emphasizing that not only obvious demographic factors but also individual characteristics may play a crucial role in internet use.